2011
DOI: 10.1371/journal.pone.0027234
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Type of HIV-1 Particle Assembly Inhibitor Using a Quantitative Luciferase-Vpr Packaging-Based Assay

Abstract: The HIV-1 auxiliary protein Vpr and Vpr-fusion proteins can be copackaged with Gag precursor (Pr55Gag) into virions or membrane-enveloped virus-like particles (VLP). Taking advantage of this property, we developed a simple and sensitive method to evaluate potential inhibitors of HIV-1 assembly in a living cell system. Two proteins were coexpressed in recombinant baculovirus-infected Sf9 cells, Pr55Gag, which formed the VLP backbone, and luciferase fused to the N-terminus of Vpr (LucVpr). VLP-encapsidated LucVp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Moreover, for the first time, a direct interaction between compound 16 and the peptide CA-SP1eNC was proved by NMR. More recently, we showed that compound 16 was able to generate an aberrant assembly of VLP, resulting in nonenveloped, morula-like particles of 100 nm in diameter [37]. All together, these data constitute a first step in the understanding of the mechanism by which bevirimat inhibits HIV-1 assembly and maturation as proposed in a previous model [27,38].…”
Section: Introductionsupporting
confidence: 52%
“…Moreover, for the first time, a direct interaction between compound 16 and the peptide CA-SP1eNC was proved by NMR. More recently, we showed that compound 16 was able to generate an aberrant assembly of VLP, resulting in nonenveloped, morula-like particles of 100 nm in diameter [37]. All together, these data constitute a first step in the understanding of the mechanism by which bevirimat inhibits HIV-1 assembly and maturation as proposed in a previous model [27,38].…”
Section: Introductionsupporting
confidence: 52%
“…AcMNPV gag expresses the full-length, wild-type, N-myristoylated HIV-1 Gag polyprotein in Sf9 cells, resulting in the assembly and extracellular release of membrane-enveloped VLPs at high yields. The high number of particles produced per cell in this heterologous model system of VLP assembly and egress, allowed quantitative analyses of morphologically normal VLPs compared to aberrant particles 31 , 33 , 48 51 .…”
Section: Resultsmentioning
confidence: 99%
“…S1). The aim of the N-myristoylation of αRep4E3-GFP and αRep9A8-GFP was to compensate for the difference in cell content between the N-myristoylated Pr55Gag polyprotein, expressed at high levels under the control of the strong polyhedrin promoter 31 , 33 , 48 51 , and αRep proteins, expressed at lower levels under the control of the weaker OpIE2 promoter. Addressing (Myr+)αRep proteins to the plasma membrane was meant to promote the interaction between Pr55Gag and αRep proteins at the assembly sites of membrane-enveloped VLPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, chemiluminescent signals obtained from this protein were very low, consistent with our own experience that HIV-1 Gag-Luciferase fusion proteins are poorly incorporated into VLPs in mammalian cells (unpublished observations). Recently, a Vpr-firefly luciferase fusion has been used to monitor HIV-1 particle release in a baculovirus-based Gag and Vpr expression system (Gonzalez et al, 2011). However this is obviously a non-native context, with highly overexpressed Gag and Vpr proteins.…”
Section: Discussionmentioning
confidence: 99%